Environmental Nanoparticles Reach Human Fetal Brains - Lilian Calderón-Garcidueñas; Ángel Augusto Pérez-Calatayud; Angélica González-Maciel; Rafael Reynoso-Robles; Héctor G. Silva-Pereyra; Andrea Ramos-Morales; Ricardo Torres-Jardón; Candelario de Jesús Soberanes-Cerino; Raúl Carrillo-Esper; Jesús Carlos Briones-Garduño; Yazmín del Socorro Conde-Gutiérrez (Biomedicines, 2022)
Anthropogenic ultrafine particulate matter (UFPM) and industrial and natural nanoparticles (NPs) are ubiquitous. Normal term, preeclamptic, and postconceptional weeks(PCW) 8–15 human placentas and brains from polluted Mexican cities were analyzed by TEM and energy-dispersive X-ray spectroscopy. We documented NPs in maternal erythrocytes, early syncytiotrophoblast, Hofbauer cells, and fetal endothelium (ECs). Fetal ECs exhibited caveolar NP activity and widespread erythroblast contact. Brain ECs displayed micropodial extensions reaching luminal NP-loaded erythroblasts. Neurons and primitive glia displayed nuclear, organelle, and cytoplasmic NPs in both singles and conglomerates. Nanoscale Fe, Ti, and Al alloys, Hg, Cu, Ca, Sn, and Si were detected in placentas and fetal brains. Preeclamptic fetal blood NP vesicles are prospective neonate UFPM exposure biomarkers. NPs are reaching brain tissues at the early developmental PCW 8–15 stage, and NPs in maternal and fetal placental tissue compartments strongly suggests the placental barrier is not limiting the access of environmental NPs. Erythroblasts are the main early NP carriers to fetal tissues. The passage of UFPM/NPs from mothers to fetuses is documented and fingerprinting placental single particle composition could be useful for postnatal risk assessments. Fetal brain combustion and industrial NPs raise medical concerns about prenatal and postnatal health, including neurological and neurodegenerative lifelong consequences.